2022
DOI: 10.3390/healthcare10061035
|View full text |Cite
|
Sign up to set email alerts
|

Breathing, (S)Training and the Pelvic Floor—A Basic Concept

Abstract: Background: The current scientific literature is inconsistent regarding the potential beneficial or deleterious effects of high-intensity physical activities on the pelvic floor (PF) in women. So far, it has not been established with certainty whether disparate breathing mechanisms may exert short- or long-term influence on the PF function in this context, although based on the established physiological interrelationship of breathing with PF activation, this seems plausible. Objective: To propose a basic conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…The thickness change of TrA muscle was greater in healthy individuals compared to SUI patients in deep expiration and coughing. IAP during expiratory efforts requires the proper function of all abdominal muscles [6]. Anatomically, TrA muscle wraps around the abdominal cavity, and the fibers are placed horizontally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness change of TrA muscle was greater in healthy individuals compared to SUI patients in deep expiration and coughing. IAP during expiratory efforts requires the proper function of all abdominal muscles [6]. Anatomically, TrA muscle wraps around the abdominal cavity, and the fibers are placed horizontally.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a weak association has been reported between PFM strength and urinary continence during tasks that increase intra-abdominal pressure (IAP) [4,5]. The PFMs do not act in isolation; instead, they are activated in synergy with other muscles surrounding the abdominal cavity during increased IAP [6].…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for suggesting breathing exercises into PFMT programs is the belief that there is a facial connections between the respiratory diaphragm and the pelvic floor. 7,8,12,21 Tim and Mazur-Bialy 50 claimed that PFM are linked by myofascial connections with the respiratory diaphragm, TrA, intercostal muscles, oblique abdominal muscles, and thoracolumbar fascia. This suggestion needs to be substantiated with evidence from basic cadaver and imaging studies of anatomy.…”
Section: Rctsmentioning
confidence: 99%
“…Due to its location at the lower part of the abdominal canister, it has been suggested that the PFM works in orchestra with abdominal muscles and the thoracic diaphragm 7,8 . Based on this some authors have suggested that “nonoptimal strategies for posture, movement, and/or breathing create failed load transfer which can lead to UI.” 9 Likewise, some authors claim that the PFM is important for breathing function, 7,10,11 and that holding the breath in an inspiratory pattern during exertion stresses the PFM and may cause pelvic floor dysfunction (PFD) 8 . In addition, it was suggested that “an expiratory motor pattern during body work‐outs and strenuous efforts is likely to protect and even train the cocontracted PFMs and lower abdominal muscles.” 8 Furthermore, Toprak et al 12 hypothesized that pelvic floor function can be improved by performing diaphragmatic breathing exercises, indirectly via what they claimed to be a facial connection between the diaphragm and PFM, and that incontinence could be reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation